Nuevo nombre en Rhodanthemum (Compositae, Anthemideae). - Gómiz García, Francisco (Acta Botanica Malacitana, 2014)
New name in Rhodanthemum (Compositae, Anthemideae). Palabras clave. Rhodanthemum redieri subsp. soriae, Leucanthemum redieri var. cuneatum, Flora, Taxonomía, Marruecos, Norte de África Key words. Rhodanthemum redieri subsp. soriae, Leucanthemum redieri var. cuneatum, Flora, Taxonomy, Morocco, North Africa.